THE INFLUENCE OF ENVIRONMENT AND LEARNING INTEREST ON THE LEARNING ACHIEVEMENT OF QURAN HADITH STUDENTS AT MUHAMMADIYAH BANTAENG ISLAMIC HIGH SCHOOL - Amal, Muh. Arvan; Malli, Rusli; Dewanti Palangkey, Rahmi (Universitas Islam Negeri Alauddin Makassar, 2024)
The purpose of this research is to determine the influence of the environment (X1) and interest (X2) on learning achievement (Y) in al-Qur'an-Hadith. This research uses a non-experimental quantitative research design with ex-post-facto causality using parametric inferential statistical analysis in the form of correlation (regression). The population in this study was all 137 students of Madrasah Aliyah Muhammadiyah Bantaeng for the 2023/2024 academic year. The sample size was determined using the purposive sampling method to obtain a sample of 31 people.The results of the research show that the learning environment has an influence on Al-Qur'an-Hadith learning achievement as shown by the results of the t test which obtained a result of 0.000 or less than <0.05 and higher than the t table value of 1.773. Interest in learning has an influence on Al-Qur'an-Hadith learning achievement as shown by the results of the t test which obtained a result of 0.021 or less than <0.05 and higher than the t table value of 1.772. The learning environment and learning interest in learning influence the learning achievement of al-Qur'an-Hadith as shown by the results of the f test which obtained a result of 0.000 or less than <0.05 and f value that was higher than the f table value of 742,050. It is known that the R Square value is 0.821, which means that the influence of the learning environment (X1) and learning interest (X2) simultaneously on the learning achievement (Y) of MA Muhammadiyah Bantaeng students is (82.1%). Future research can further analyze the influence of several domains included in the question of learning environment variables and learning interest variables. Future research can carry out in-depth information mining using mixed method research methods.